1998
DOI: 10.1089/mdr.1998.4.301
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Genetic Relatedness of InvasiveHaemophilus influenzaeType b in Italy

Abstract: Haemophilus influenzae type b (Hib) still causes a large portion of meningitis in children less than 5 year old in Italy because vaccination against this agent has not been fully implemented in the country. We have studied 78 Hib strains and 4 nontypable H. influenzae (NTHi) isolated from the cerebrospinal fluid of subjects with meningitis for susceptibility to ampicillin, chloramphenicol, and ceftriaxone. The macrorestriction profiles of chromosomal DNA obtained by pulsed-field gel electrophoresis (PFGE) foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
4
19
0
Order By: Relevance
“…Additionally, the most common PFGE type, A, characterized more than 95% of the Hib isolates, and the most common PFGE subtype, A1, was also the most prevalent among isolates responsible for invasive disease in Italy and the Czech Republic and among isolates causing lower respiratory tract infections in Poland (28,32). Thus, the results of this study support the evidence that the genetic structure of encapsulated H. influenzae is clonal.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Additionally, the most common PFGE type, A, characterized more than 95% of the Hib isolates, and the most common PFGE subtype, A1, was also the most prevalent among isolates responsible for invasive disease in Italy and the Czech Republic and among isolates causing lower respiratory tract infections in Poland (28,32). Thus, the results of this study support the evidence that the genetic structure of encapsulated H. influenzae is clonal.…”
Section: Discussionsupporting
confidence: 80%
“…In the light of the above data, the percentage of ␤-lactamase producers among Polish meningitis isolates is not very high, although it is three times higher than found among H. influenzae isolates responsible for lower respiratory tract infections in Poland (28). The observation that antibiotic resistance is more prevalent in encapsulated isolates, responsible for the majority of meningitis cases, than in nontypeable H. influenzae was also revealed by other authors (4,10,32). The results of some studies showed that there is also an increasing number of H. influenzae isolates resistant to chloramphenicol (e.g., Bangladesh, 21.5%; Paraguay, 20%; Cuba, 44%) and an increasing number of isolates resistant simultaneously to both mentioned antibiotics (2,26,31).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Thus, they suggested that the population structure of capsulate H. in¯uenzae is basically clonal and that most infections are caused by a small number of clonal genotypes. The results obtained in the present study support the previous ®ndings [21,22]. Different riboprinter patterns were obtained for non-type b and non-typable H. in¯uenzae isolates.…”
Section: Taipei (30)supporting
confidence: 92%